2005
DOI: 10.1074/jbc.m409176200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Estrogen-responsive Genes Using a Genome-wide Analysis of Promoter Elements for Transcription Factor Binding Sites

Abstract: We developed a pipeline to identify novel genes regulated by the steroid hormone-dependent transcription factor, estrogen receptor, through a systematic analysis of upstream regions of all human and mouse genes. We built a data base of putative promoter regions for 23,077 human and 19,984 mouse transcripts from National Center for Biotechnology Information annotation and 8793 human and 6785 mouse promoters from the Data Base of Transcriptional Start Sites. We used this data base of putative promoters to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…The same element has been found by a systematic genome-wide bioinformatic study by analyzing promoter elements for transcription factor binding sites with the aim of identifying estrogen-responsive genes (169). However, the regulation of ABCG2 seems to be cell line specific, because it is actually downregulated following estrogen treatment in ER-positive MCF7 cells (169). Moreover, as mentioned below, estrogen regulation of ABCG2 may be mostly of posttranslational nature.…”
Section: Regulation Of Abcg2mentioning
confidence: 77%
“…The same element has been found by a systematic genome-wide bioinformatic study by analyzing promoter elements for transcription factor binding sites with the aim of identifying estrogen-responsive genes (169). However, the regulation of ABCG2 seems to be cell line specific, because it is actually downregulated following estrogen treatment in ER-positive MCF7 cells (169). Moreover, as mentioned below, estrogen regulation of ABCG2 may be mostly of posttranslational nature.…”
Section: Regulation Of Abcg2mentioning
confidence: 77%
“…Thus, this transporter is unlikely to be associated with drug resistance in the single-step-selected clones. Using PAGen@UIC (www.uic.edu/pharmacy/depts/pmpcpd/pagen/), we found that there are 11 predicted transcription factors that have binding sites on the promoters of both ABCG2 and ABCC4 (Kamalakaran et al, 2005). Thus, it is possible that the coordinate overexpression of both transporters may be due to an effect of common transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis of gene promoters, using software trained to identify consensus TF recognition sequences, has proved of great use in detecting functional TF binding sites (Tullai et al, 2004;Chowdhary et al, 2005;Kamalakaran et al, 2005;Xie et al, 2005;Zhang et al, 2005). To assess the likelihood that the identified genes are direct targets of Zif268, we assessed the abundance of consensus EREs in the genomic region 1 kb upstream of the TSS of 24 proteasome-related genes identified as potential Zif268 targets compared with 20 randomly selected genes (see Materials and Methods) (Table 2), using the program MatInspector (Quandt et al, 1995).…”
Section: Bioinformatic Analysis Of Zif268-regulated Proteasome Genesmentioning
confidence: 99%